The Role of Supporting Entrepreneurial Mechanisms in the Ljubljana Urban Region: The Case of Poni Lur - Raspor Josipovič, Črtomir; Josipovič, Damir; Marinčič, Dejan (Improving Entrepreneurial Journey, 2025)
In this paper, we explore the role of supportive entrepreneurial mechanisms in improving the entrepreneurial experience of participants in the PONI LUR program, implemented by the Regional Development Agency of the Ljubljana Urban Region. We analyzed the socio-demographics of the program participants and their decisions to pursue an independent entrepreneurial path and their attitudes towards it. We found that 62% of participants established their own company after completing the program, with micro-enterprises in the service sector dominating. Participants highlighted the importance of access to mentoring, financing, practical workshops, and networking, which confirms the theoretical framework of entrepreneurial ecosystems and the importance of social capital. The results of our research reveal that the success of such development programs is closely related to the creation of an inclusive supportive environment and the strengthening of entrepreneurial self-confidence. Program participants usually already develop motivations that they can implement more successfully with appropriate support. Testing the four hypotheses set out in summary showed that higher formal education does not necessarily increase the likelihood of starting a business, and that within the framework of LUR, participants from the MOL area more often decide on an entrepreneurial path. Previous entrepreneurial experience did not have a decisive impact on the sustainability of companies. The majority of respondents (94%) would recommend the program to others, which confirms its quality.